ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN PT. CALMIC INDONESIA DI AREA JAKARTA. - Tukidi, Tukidi; Romadhon, Patchu; Adhani, Ida (Management Research and Business Journal, 2023)
ABSTRACT This study aims to determine the Effect Analysis of Product Quality, Price and Brand Image on Customer Satisfaction of PT. Calmic Indonesia in the Jakarta Area. Based on the results of the multiple linear regression test, it produces the equation Y = 2.053 + 0.090X1 + 0.184X2 + 0.687X3 + e. From the results of the t test the Product Quality Variable (X1) has a tcount value of 1.338 < ttable of 1.99656 and a significance level value of 0.186 > 0.05. Then Ha1 is rejected and Ho1 is accepted, so that it has no significant effect partially between the variable Product Quality (X1) on Customer Satisfaction (Y). The price variable (X2) has a tcount value of 1.470 <table of 1.99656 and a significance level of 0.146 > 0.05. Then Ha2 is rejected and Ho2 is accepted, so there is no significant effect partially between the Price variable (X2) on Customer Satisfaction (Y). The brand image variable (X3) has a tcount value of 5.454 > table 1.99656 and a significance level of 0.000 <0.05. Then Ha3 is accepted and Ho3 is rejected, so that it has a partially significant effect between Brand Image variables (X3) on Customer Satisfaction (Y). From the results of the calculation of the F test statistic, it shows that the Fcount value is 63.764 > Ftable is 2.74 and the significance value is 0.000 <0.05. This means that Ha4 is accepted and Ho4 is rejected, meaning that there is a simultaneous influence between Product Quality, Price and Brand Image on Customer Satisfaction at PT. Calmic Indonesia in the Jakarta Area. And from the results of the calculation of the adjusted R square value in the table it is 73.2%. Customer satisfaction is explained by product quality, price and brand image of 73.2% with the remaining 27.8% explained by other variables not explained in this study such as the marketing mix and other marketing strategies.